COVID-19, Changes in Educational Practices and the Perception of Stress by University Educators in Latin America – a Post-pandemic Analysis - Frango-Silveira, Ismar (2023)
The COVID-19 pandemic brought about profound changes in social and professional contexts. Schools and universities all over the world were closed to curb the contamination. In a short period, many educators were forced to reinvent their classes in a non-classroom mode, mediated by technology. This scenario of overwork can lead educators to stress, favoring distress, anxiety, and depression due to the uncertainties resulting from the pandemic and the search for new knowledge acquisition. This paper shows the research results conducted by university educators in Latin America who have been exercising teaching activities during social isolation imposed by COVID-19. The results show that with just one exception, educators from all countries reported suffering from some stress-related aspects concerning some manner to remote teaching. Higher workload perception came from women, unfolding gender inequalities amplified during pandemics. There is no clear relationship between the degree of technological expertise and stress factors, although, in general, educators use more time to prepare learning material and monitor students’ progress. Technological infrastructure was not a big concern for those educators in big cities, but some fundamental infrastructure problems were reported due to each country’s economic reality or geographic conditions.